Barriers to Advocacy and Litigation in the Equality Courts for Persons with Disabilities - Holness, Willene; Rule, Sarah (Potchefstroom Electronic Law Journal, 2017)
The effective implementation of the Promotion of Equality and Prevention of Unfair Discrimination Act 4 of 2000 (PEPUDA) and the fulfilment of the South African state’s obligations in terms of the Convention on the Rights of Persons with Disabilities (CRPD) are dependent on two fundamental tools, advocacy and litigation. This article discusses the outcome of three cases in the Equality Courts and how these cases promote accessibility and access to justice for persons with disabilities. The authors then consider the impact of CREATE, a KwaZulu-Natal NGO’s advocacy initiatives to promote the rights of persons with disabilities and the utilisation of the Equality Court to realise those rights. Participants of ten workshops in KwaZulu-Natal identified three barriers to access to justice in accessing the Equality Courts. Firstly, some Equality Courts are geographically (and financially) inaccessible. Secondly, the negative and insensitive attitudes of front-line workers impact on the ability of persons with disabilities to bring equality claims to and access the services of the Equality Court. These barriers constitute discrimination and flout articles 9 and 13 of the CRPD, which require the provision of support for persons with disabilities to access the justice system and the promotion of accessibility to the physical environment, and the provision to them of transportation, information and other services. Thirdly, cultural norms and fears impede access to courts and the agency of persons with disabilities to bring these claims, for example the requirement that traditional leaders provide "permission" to persons with disabilities to sue and a similar requirement of permission from the in-laws of women with disabilities. The article analyses the three barriers identified as inhibiting advocacy and litigation, and explains the implication of these barriers for the state’s obligations in terms of articles 5, 8, 9, 12 and 13 of the CRPD. Recommendations are made on overcoming these barriers.